Design and Development of Android-based interactive 3D Virtual Tours for Campuses - Adisusilo, Anang (International Journal of Science, Technology & Management, 2024)
Virtual Tour has become a popular simulation in virtual reality (VR) technology by combining a series of images to produce 360-degree panoramic photos. By taking objects in the Wijaya Kusuma University Surabaya campus environment, the Virtual Tour can introduce the social and physical environment to new students and the general public. This research aims to enable users to feel like they are in the campus environment through the virtual world. The virtual world environment is created in 3 dimensions, which contains an explanation of the object to be targeted; for software design using programming algorithms in the C# language, a finite state machine (FSM) is created in designing the player control system, 3D Blender in creating three-dimensional objects and using Unity 3D in building applications. The research results show an innovation in the form of a 3D virtual tour of Wijaya Kusuma University Surabaya using the Unity 3D platform, which allows users to interact with the campus environment through smooth movements using a virtual joystick. This virtual tour allows users to explore the university in depth by walking around the campus to find important places at Wijaya Kusuma University Surabaya.